(untitled) (Vietnam Journal of Community Medicine, 2025)
Carney complex is a dominant genetic disease associated with many neoplasm in multiple endocrine glands such as the thyroid, pituitary, and adrenal glands and tumors outside the endocrine glands. Typically, patients have many brown pigmented spots on the face and many tumors in the heart, breast, adrenal glands... The most common heart tumor is atrial myxoma and can recur many times. Patients also have symptoms of Cushing’s syndrome in many cases. Confirmed diagnosis is often missed. We report a typical case and review the literature on this disease.